Tugas Keluarga dan Perilaku Pencegahan Komplikasi Hipertensi pada Lansia - I Dewa Putu Gede Putra Yasa; Ketut Sudiantara (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
The objective of study is to now correlation between health family task and behaviour of complication prevention of hypertension elderly. Design of study is descriptive correlation with cross sectional approach. Study is located at Public Health Centre III of Nort of Denpasar on 2012 with 40 respondent was selected by using Simple Random Sampling. The result of study showed 87.5% had good level of family task and 77.5% had good level of bahaviour of complication prevention. There are significant strong correlation between health family task and behaviour of complication prevention of hypertension elderly (p=0.000, r = 0.702)